DEVELOPMENT OF CANDIDATE REFERENCE MATERIALS FOR CONTENT ANALYSIS OF METAL OXIDES COAL BOTTOM ASH - Amelianawati, Mae
Coal bottom ash ( Bottom Ash ) is the result of waste coal burning furnaces that are at the bottom . The study of coal ash from the policy to the attention of researchers , particularly for quality control analysis needs . At the completion of this research study for the determination of candidate reference material oxide content of coal bottom ash ( bottom ash ) using X-ray Fluorescence Spectrometry ( XRF ) and as the comparator method is ASTM D- 3682 method . Completion of coal bottom ash as a candidate reference material consists of several levels, namely heating , attenuation measurements, sieving ( 200 mesh) , and sample packaging division , for possible further testing sample homogeneity level . Samples used is derived from coal combustion bottom ash results in PT . Pindodelli Pulp and Paper Mills , Karawang regency , West Java . General character of the water is measured . Water rates are determined by heating 1 gram sample using the oven at 1050C for ± 2 hours with the results of measurements of water samples around 0.04 % - 0.08 % . In this study , homogeneity test performed on each chemical element . XRF analysis results obtained using the oxide content of SiO2, Al2O3 , Fe2O3 , CaO , MgO , K2O , TiO2 , Na2O , MnO , Cr2O3 , P2O5 , Bao , V2O5 , ZnO , NiO , SRO , and SO3 . In this study, also done oxide content measurement using a standard method ASTM D- 3682 . Measurement using Atomic Absorption Spectrophotometer instrument ( SAA ) with measurable elements namely Fe2O3 , CaO , MgO , K2O , and Na2O . Use of SSA method provides reliability repeated measurements give quite good , with RSD range for 8 samples at the specified element respectively is : Fe2O3 , MgO , Na2O , CaO , and K2O is 0.57 % -1.28 % , 0 , 9 % - 4.48 % , 0 % - 0.19% , 0 % - 2.18 % , and 1.33 % - 3.33 % . Measurement of each element studied , further comparison between the XRF and AAS . Compare test results using the t- student test with 95% confidence that the results of the analysis of samples showed mold material candidates using XRF and SSA significantly different , so that the values obtained can not be the mold , but just as the value of information .